Social protection and poverty reduction: Increasing the benefits of MGNREGS for children - Kumar, V (Young Lives, 2013)
The World Bank describes social protection as having preventive, protective and promotive aims. Key to the objectives of social protection policies is the need to prevent income shocks, to protect those with inadequate resources, and to promote opportunities that can help households improve their situation. Young Lives analysis shows the impact of the Mahatma Gandhi National Rural Employment Guarantee Scheme in India on families’ ability to cope with shocks and adverse events, acquire productive assets, and invest in children’s well-being. It has significantly higher coverage than previous public works programmes, and better inclusion of women and marginalised groups. Some of the positive impacts claimed for the scheme are that it protects people from hunger, reducing distress migration, empowering women, and creating useful assets. However there remain important challenges to be addressed to maximise the positive impacts on children’s well-being.